1989
DOI: 10.21236/ada212756
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of an 85 GHz Gyrotron to Operate at 94 GHz

Abstract: la REPORT SECURITY CLASSIFICATION lb RESTRICTIVE MARKINGS UNCLASSIFIED 2a. SECURITY CLASSIFICATION AUTHORITY 3. DISTRIBUTION /AVAILABILITY OF REPORT Approved for public release; distribution 2b. DECLASSIFICATION I DOWNGRADING SCHEDULE unlimited. 4. PERFOORMING ORGANIZATION REPORT NUMBER(S) 5 MONITORING ORGANIZATION REPORT NUMBER(S) NRL Memorandum Report 6513 6a NAME OF PERFORMING ORGANIZATION 6b OFFICE SYMBOL 7a. NAME OF MONITORING ORGANIZATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…A decrease in the Hα luminosity of IC 3599 by a factor of 10 in less than a year (Mannheim et al 1996) is perhaps independent evidence that the total ionizing luminosity of this object does vary by a large factor. On the other hand, there were no significant changes in the optical continuum flux or Fe II line intensities in PHL 1092 between optical spectra coincidentally taken in 1979 August (Bergeron & Kunth 1980, 1984 one month after the Einstein observation, and in 1992 September (Kwan et al 1995) eight months after ROSAT observed the QSO in its X-ray high state.…”
Section: Long-term Variabilitymentioning
confidence: 78%
See 1 more Smart Citation
“…A decrease in the Hα luminosity of IC 3599 by a factor of 10 in less than a year (Mannheim et al 1996) is perhaps independent evidence that the total ionizing luminosity of this object does vary by a large factor. On the other hand, there were no significant changes in the optical continuum flux or Fe II line intensities in PHL 1092 between optical spectra coincidentally taken in 1979 August (Bergeron & Kunth 1980, 1984 one month after the Einstein observation, and in 1992 September (Kwan et al 1995) eight months after ROSAT observed the QSO in its X-ray high state.…”
Section: Long-term Variabilitymentioning
confidence: 78%
“…It has long been known that there are high-luminosity analogs of this class, the prototype of which is I Zw 1 (e.g., Phillips 1976), which also have weak forbidden lines, narrow permitted lines, and strong Fe II. One of the most extreme narrow-line Fe II QSOs is PHL 1092 (Bergeron & Kunth 1980, 1984Kwan et al 1995). Its Fe II λ4570/Hβ ratio is 5.3, and its line widths are only 1800 km s −1 (Bergeron & Kunth 1984).…”
Section: Introductionmentioning
confidence: 99%
“…respect to older spectra (e.g. Bergeron & Kunth 1980). Here we compare the two HET optical spectra of PHL 1092 which were obtained in 2008 and 2010.…”
Section: Optical Het Spectra: Comparison Between the 2008 And 2010 Obmentioning
confidence: 99%
“…Here we consider the case of PHL 1092 which recently became one of the most extreme X-ray weak non-BAL quasars known (see below). PHL 1092 (z = 0.396) is a radio-quiet quasar with outstanding Fe II emission (Bergeron & Kunth 1980, 1984Kwan et al 1995). Its broad line widths of ∼1800 km s −1 and a ratio [O III]λ5007/Hβ ∼ 0.9, together with the strong Fe II emission (Fe II/Hβ = 1.81), classify PHL 1092 as a high-luminosity Narrow-Line Seyfert 1 (NLS1) galaxy (Osterbrock & Pogge 1985).…”
mentioning
confidence: 99%
“…PHL 1092 (B = 16.7; z = 0.396) is a luminous Narrow-Line Seyfert 1 (NLS1) class quasar that is one of the strongest optical Fe ii emitters known (Bergeron & Kunth 1980). Such objects have been generally found to have extreme X-ray spectral and variability properties, and it appears likely that their exceptional X-ray/optical characteristics arise as the result of an extreme value of a primary physical parameter (see Brandt & Boller 1998 for a recent discussion).…”
Section: Introductionmentioning
confidence: 99%